Correlation between volumetric oxygen transfer coefficient and power requirement in citric acid fermentation by aspergillus niger - Hassan, Mohd Ali; Nik Sin, Nik Daud; Abdul Ghani, Baharuddin; Abdul Karim, Mohamed Ismail (Universiti Putra Malaysia Press, 1995)
A batch culture system for the production of citric acid by Aspergillus niger TISTR 3089 was studied to determine the effect of aeration and mixing on the volumetric oxygen transfer coefficient (kLa) and power requirement. A 2-l batch stirred-tank was used with impeller speeds of500-900 -rpm at an aeration rate of 0.65 vvm with glucose as the carbon source. kLa and power consumption varied with duration offermentation. The data obtained were fitted to mathematical correlations between kLa and power requirement during gassing per unit volume of liquid (Pg/V) and superficial gas velocity reported by previous researchers. By including the agitator speed, better correlations were obtained, indicating the importance of stirrer speed in such correlations. The proposed relationship is: kLa = k (Pg/V)0.95 U0.67 N0.5, where U is the superficial gas velocity and N is the stirrer speed.